Stabilizing atomic Pt with trapped interstitial F in alloyed PtCo nanosheets for high-performance zinc-air batteries. Issue 3 (10th December 2019) - Li, Zhao; Niu, Wenhan; Yang, Zhenzhong; Zaman, Nusaiba; Samarakoon, Widitha; Wang, Maoyu; Kara, Abdelkader; Lucero, Marcos; Vyas, Manasi V.; Cao, Hui; Zhou, Hua; Sterbinsky, George E.; et al.
Abstract : A novel strategy is designed to stabilize atomic Pt catalysts in alloyed platinum cobalt nanosheets with trapped interstitial fluorine (SA-PtCoF) for zinc-air batteries. Abstract : Recently, considerable attention has been paid to the stabilization of atomic platinum (Pt) catalysts on desirable supports in order to reduce Pt consumption, improve the catalyst stability, and thereafter enhance the catalyst performance in renewable energy devices such as fuel cells and zinc-air batteries (ZABs). Herein, we rationally designed a novel strategy to stabilize atomic Pt catalysts in alloyed platinum cobalt (PtCo) nanosheets with trapped interstitial fluorine (SA-PtCoF) for ZABs. The trapped interstitial F atoms in the PtCoF matrix induce lattice distortion resulting in weakening of the Pt–Co bond, which is the driving force to form atomic Pt. As a result, the onset potentials of SA-PtCoF are 0.95 V and 1.50 V for the oxygen reduction and evolution reactions (ORR and OER), respectively, superior to commercial Pt/C@RuO2 . When used in ZABs, the designed SA-PtCoF can afford a peak power density of 125 mW cm −2 with a specific capacity of 808 mA h gZn −1 and excellent cyclability over 240 h, surpassing the state-of-the-art catalysts.